Sistem Informasi Manajemen Paud Melati Di Desa Lebak Ayu Kecamatan Sawahan Kabupaten Madiun Berbasis Web - LUKMAN NUL HAKIM (LPPM Universitas Merdeka Madiun, 2024)
PAUD Melati is one of the early childhood education level schools located in Lebak Ayu Village, Sawahan District, Madiun Regency. The problem with PAUD Melati is the process of collecting new student data and teaching and learning processes which are still manual, so what is considered is still not systematic and at the time of reporting and archiving documents it is still done with written document archives. Therefore, an early childhood management information system was built to facilitate school management to be more effective and efficient. The management information system was built and designed using the Waterfall method and tested using the Black Box Testing system testing method. With this PAUD management information system, it is hoped that it will be able to assist the school in carrying out the registration process to teaching and learning activities. The test results of the Web-Based Melati Early Childhood Education Management Information System get the expected results with the Black Box Testing test to get a percentage of system success of 100%.